Meta-analyses identify DNA methylation associated with kidney function and damage - Schlosser, Pascal; Tin, Adrienne; Matias-Garcia, Pamela R.; Thio, Chris H. L.; Joehanes, Roby; Liu, Hongbo; Weihs, Antoine; Yu, Zhi; Hoppmann, Anselm; Grundner-Culemann, Franziska; Min, Josine L.; Adeyemo, Adebowale A.; et al. (Nature Communications, 2021)
Chronic kidney disease is a major public health burden. Elevated urinary albumin-to-creatinine ratio is a measure of kidney damage, and used to diagnose and stage chronic kidney disease. To extend the knowledge on regulatory mechanisms related to kidney function and disease, we conducted a blood-based epigenome-wide association study for estimated glomerular filtration rate (n = 33,605) and urinary albumin-to-creatinine ratio (n = 15,068) and detected 69 and seven CpG sites where DNA methylation was associated with the respective trait. The majority of these findings showed directionally consistent associations with the respective clinical outcomes chronic kidney disease and moderately increased albuminuria. Associations of DNA methylation with kidney function, such as CpGs at JAZF1, PELI1 and CHD2 were validated in kidney tissue. Methylation at PHRF1, LDB2, CSRNP1 and IRF5 indicated causal effects on kidney function. Enrichment analyses revealed pathways related to hemostasis and blood cell migration for estimated glomerular filtration rate, and immune cell activation and response for urinary albumin-to-creatinineratio-associated CpGs.